Penerapan Media TAMAN BUDI untuk Meningkatkan Hasil Belajar Siswa Kelas V-A pada Pelajaran Pendidikan Pancasila - Zein, Mira Anggraini; Mushlihuddin, Rahmat; Handhayani, Wury (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the implementation of interactive and innovative learning media that are contextually grounded and culturally responsive in Pancasila Education at the elementary school level, despite the significant impact such approaches have on student engagement and learning outcomes. The aim of this research is to determine the effectiveness of using the Peta Keberagaman Budaya Indonesia (TAMAN BUDI) media in improving student learning outcomes on the topic of diversity as a strength. The method used is Classroom Action Research (CAR) with a descriptive quantitative design, conducted in two cycles. The research subjects consisted of 26 fifth-grade students at SD Negeri 060913 Medan, selected through purposive sampling. Data collection techniques included interviews, observation, and testing, analyzed using descriptive percentage analysis. The results show a significant increase in student activity from 65.61% in Cycle I to 80.11% in Cycle II, and mastery of learning outcomes improved from 54% to 65%. The average class score also rose from 66.96 to 80.38. These findings support constructivist theory and Culturally Responsive Teaching, both of which emphasize active student engagement and the relevance of local context in learning. In conclusion, TAMAN BUDI media is effective in enhancing learning outcomes and fostering students’ appreciation of Indonesia’s cultural diversity. The implications include a theoretical contribution to the literature on local wisdom-based media and practical recommendations for teachers to optimize contextual media for more meaningful Pancasila Education. This study also opens opportunities for further exploration across different subjects and educational levels.